2012
DOI: 10.1002/eji.201242590
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity‐mediated antitumor immunity: Tumor as an immunoprivileged self

Abstract: IntroductionA cardinal capacity of the immune system is to differentiate between "self", the body's own tissue, and "non-self", exemplified by microbial infectious agents. Malignant tumor tissues present a distinct challenge to the immune system as "altered self".Correspondence: Dr. Zhibin Chen e-mail: zchen@med.miami.edu Antigenic proteins from mutated genes in cancer cells, or viral products from transformed tumor cells, may trigger the immune system as tumor-specific antigens (TSAs) that are not expressed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…The concept of cancer immune surveillance is based on the hypothesis that the immune system can suppress the development or progression of spontaneous malignancies [5]. Several data, first from animal models and later from studies in cancer patients, confirmed this original concept that the immune system can recognize and reject tumors, supporting the hypothesis that immune evasion by cancer cells plays an important role in the development and progression of tumors [6].…”
Section: Immune Evasion As Hallmark In Cancermentioning
confidence: 96%
“…The concept of cancer immune surveillance is based on the hypothesis that the immune system can suppress the development or progression of spontaneous malignancies [5]. Several data, first from animal models and later from studies in cancer patients, confirmed this original concept that the immune system can recognize and reject tumors, supporting the hypothesis that immune evasion by cancer cells plays an important role in the development and progression of tumors [6].…”
Section: Immune Evasion As Hallmark In Cancermentioning
confidence: 96%
“…Although CTLA4 blockade led to increased motility of CD4 + BDC2.5 T eff and T reg cells in T reg cell-protected grafts, it decreased the motility of CD8 + OT1 T eff cells. Moreover, in a model wherein CTLA4 in CD8 + OT1 T eff cells were modulated with RNAi (Chen et al, 2006;Miska et al, 2012), CTLA4 reduction decreased motility of T eff cells, suggesting an intrinsic effect of CTLA4 in T eff cell motility ( Fig. 10 and Videos 5 and 6).…”
Section: Ar Ticlementioning
confidence: 93%
“…PL4 (Chen et al, 2006), OT1 (Hogquist et al, 1994), RIP-mOVA (Kurts et al, 1996), MIP-CFP (Hara et al, 2006) and CAG-CFP (Hadjantonakis et al, 2002) transgenic lines were described previously. The CTLA4shRNA and PL4 lines were backcrossed onto B6 background for >10 generations (Miska et al, 2012). The CTLA4shRNA transgene caused 2-3-fold reduction in CTLA4 expression.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, tumors present an immunoprivileged self that can suppress potent autoimmune damage. [32][33][34] On the other hand, the genome instabilities of tumor cells also produce mutations that generate potential neoantigens. 35 It would be interesting to examine whether conversion from CD8 T cells to CD4 CI-T reg cells occurs in the tumor microenvironment, not only in gastrointestinal cancer, but also in cancer in general, especially in settings of adoptive CD8 T cell therapies.…”
Section: Implications To Other Conditions Of Immunerelated Disordersmentioning
confidence: 99%